Survival and Freedom From Reinterventions in Patients With Repaired Tetralogy of Fallot: Up to 42-Year Follow-Up of 917 Patients - Gebauer, Roman; Chaloupecký, Václav; Hučín, Bohumil; Tláskal, Tomáš; Komárek, Arnošt; Janoušek, Jan (Journal of the American Heart Association, 2023)
Background To evaluate long-term outcome of tetralogy of Fallot repair analyzing an unbiased country-wide surgically treated population with tetralogy of Fallot. Methods and Results Retrospective analysis of consecutive patients aged <18 years who underwent tetralogy of Fallot repair at a single nationwide pediatric cardiac center. Death from any cause and need for surgical or catheter reintervention were the study end points. Cox regression analysis was used to identify related risk factors. A total of 917 patients (male, 56.3%) were analyzed. Staged repair was performed in 16.9%. Early mortality (24/917, 2.62% patients) was confined to the early surgical eras. Late mortality was 4.5% (40/893 patients). Survival probability was 95.1%, 93.8% and 91.9% at 10, 20 and 30 years after repair, respectively. Early surgical era (P=0.013) and surgical/catheter reinterventions (P<0.001) were multivariable predictors of late death. A total of 487 reinterventions were performed after initial repair in 253/917 patients (27.6%), with pulmonary artery revalvulation (196/917 patients, 21.4%) being most frequent. Probability of freedom from first reintervention was 89.0%, 73.3%, and 55.1% at 10, 20, and 30 years after primary repair, respectively. Transannular repair was associated with the need for pulmonary artery revalvulation (P<0.001). Patients who underwent staged repair were more likely to need reinterventions on pulmonary arteries (P<0.001). Conclusions In an unbiased nationwide cohort, tetralogy of Fallot repair carried a favorable survival of >90% at 30 years. Each reintervention significantly incrementally increased the risk of mortality. Type of initial repair predicted the need for specific surgical or catheter reinterventions.
Keywords: dítě; outcome; Treatment Outcome; Retrospective Studies; Tetralogy of Fallot; tetralogy of Fallot; lidé; Risk Factors; následné studie; reoperace; kojenec; Fallotova tetralogie; výsledek terapie; Reoperation; Male; Pulmonary Valve; Humans; Child; mužské pohlaví; plicní chlopeň; pulmonary valve replacement; Follow-Up Studies; rizikové faktory; Infant; Freedom; surgical repair; svoboda; retrospektivní studie